2012
DOI: 10.1590/s0102-695x2012005000059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depth on growth and pigment contents of the macroalgae Gracilaria bursa-pastoris

Abstract: Abstract:The effects of environmental parameters on biomass, growth and pigment content of the red seaweed Gracilaria bursa-pastoris (S.G. Gmel.) P.C. Silva was investigated under fi eld conditions in Thau Lagoon (France). The seaweed was cultivated in cages placed at three depths (1.0, 2.0 and 4.0 m) over a one-year period. The results showed elevated biomass and growth values in the spring and autumn, when temperature, light and photoperiod values were similar. The highest specifi c growth rates (SGR) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
3
4
0
1
Order By: Relevance
“…In rhodophytes, phycobiliproteins such as phycocyanin and especially phycoerythrin, are also involved in light harvesting as accessory pigments (Gómez et al., ). The results of our study show that Chl‐ a and phycoerythrin concentrations were higher at increasing water depths, coinciding with previous observations for most macroalgae (Hanelt & Figueroa, ; Marinho‐Soriano, ). This positive correlation between photosynthetic pigments and depth may result from a compensatory strategy to increase the efficiency of light harvesting in deeper waters (Gómez et al., ; Marinho‐Soriano, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In rhodophytes, phycobiliproteins such as phycocyanin and especially phycoerythrin, are also involved in light harvesting as accessory pigments (Gómez et al., ). The results of our study show that Chl‐ a and phycoerythrin concentrations were higher at increasing water depths, coinciding with previous observations for most macroalgae (Hanelt & Figueroa, ; Marinho‐Soriano, ). This positive correlation between photosynthetic pigments and depth may result from a compensatory strategy to increase the efficiency of light harvesting in deeper waters (Gómez et al., ; Marinho‐Soriano, ).…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study show that Chl‐ a and phycoerythrin concentrations were higher at increasing water depths, coinciding with previous observations for most macroalgae (Hanelt & Figueroa, ; Marinho‐Soriano, ). This positive correlation between photosynthetic pigments and depth may result from a compensatory strategy to increase the efficiency of light harvesting in deeper waters (Gómez et al., ; Marinho‐Soriano, ). By contrast, in algae living in shallow habitats the smaller antennae size (e.g., increased Chl a : b ratio or phycobiliproteins/Chl‐ a ratio) reduces the risk of overexcitation (Hanelt & Figueroa, ; Kirk, ).…”
Section: Discussionsupporting
confidence: 92%
“…This will, eventually, lead to the synthesis and accumulation (or storage) of various organic proximate products. These results agreed with Marinho-Soriano (2012), who demonstrated the important role of nitrogenous nutrients in pigment biosynthesis. And also with Xu et al ( 2020) who stated the sufficiency of nitrogenous compounds for the production of chlorophyll and phycobiliproteins as protective substances.…”
Section: Seasonal Variation In the Pigment Content Of The Collected C...supporting
confidence: 92%
“…Pereira et al (2012) found that nitrate was assimilated as PC and PE by Porphyra dioica Brodie and Irvine and phycoerythrin PE was the main form of nitrogen pool, while, phosphorus participates in the formation of biomolecules such as nucleic acids, proteins and phospholipids. In the same year, Marinho-Soriano (2012) showed the importance of NO 3 for the biosynthesis of this pigment, demonstrated the positive correlation between them.…”
Section: Discussionmentioning
confidence: 85%